Volcanic Hazards in the Pacific Northwest - Miller, C. (Geoscience Canada, 1990)
Summary The Cascade Range stretches from south-western British Columbia to northern Califor-nia; the Range consists of major composite volcanic centres, most of which have been active during late Pleistocene and Holocenetime. In addition, thousands of smaller basaltic or basaltic-andesite volcanoes have been active during the past few million years. Flow-age and tephra hazards associated with future eruptions of composite volcanoes in theRange will endanger communities located within about 50 km of erupting volcanoes.Significant effects will extend to still greater distances down wind from the volcanoes and along stream valleys that head at the volcanoes. Volcanic-hazard assessments and hazard-zonation maps developed for volcanoes in the Range can be used by authorities for long-range land-use planning and provide information to help mitigate the effects of future eruptions.